Characteristics of Al2O3-Pt/YSZ-Pt Double Layer Composite Coatings Prepared by Cathode Plasma Electrolytic Deposition. Issue 12 (December 2018) - Shunjie, Deng; Chi, Jiang; Tianwei, Liu; Maobing, Shuai; Peng, Wang
Abstract: Al2 O3 -Pt/YSZ-Pt double layer composite coatings were prepared by cathode plasma electrolytic deposition (CPED) on the superalloy with a NiCoCrAlY bond-coat. The composite coatings consist of an Al2 O3 -Pt film and a YSZ-Pt top-coat and show a good adhesion to the metallic bond-coat. It is demonstrated, from the cyclic oxidation test and mechanical properties test, that such coatings possess good oxidation and spallation resistance. These beneficial results can be attributed to these effects: owing to the extremely low oxygen diffusion rate of Al2 O3 -Pt film, such composite coatings can inhibit further oxidation of the bond-coat; the mechanical properties of Al2 O3 -Pt/YSZ-Pt composite coating are improved by the toughening effect of Pt particles.